On trans-genres or Nick Cave without Laibach at the coronation of Charles III - Marjanić, Suzana (Poznańskie Studia Slawistyczne, 2025)
A dyadicly conceived text, which is created as a comparison of the reaction of the Australian musician Nick Cave and the Slovenian band Laibach to the coronation of Charles III, or in general to the concept of the British Empire as the ultimate symbol of empire today, with a transition to the interpretation of the anarcho-performances of the Croatian transmedia artist Željko Kipke, his anti/auto-lexicon, and Vladimir Dodig Trokut’s Anti-museum and anti-monography, is interpretatively based on the ideas of Mary Douglas on the society (including the associated theory, the free interpretation) which has a weak group and a weak grid (matrix). The aforementioned transgenres, in parallel with Nick Cave’s blog and Laibach’s anti-hymns, can serve as free platforms for criticism of genre boundaries in the form of trans-genre (blog-apology; blog-reasoning, anti-hymn, anti-lexicon, Anti-museum, anti-monography).